2001
DOI: 10.1590/s1516-44462001000500011
|View full text |Cite
|
Sign up to set email alerts
|

PET e SPECT cerebrais na avaliação dos estados demenciais

Abstract: Rev Bras Psiquiatr 2001;23(Supl I):36-7 PET e SPECT cerebrais na avaliação PET e SPECT cerebrais na avaliação PET e SPECT cerebrais na avaliação PET e SPECT cerebrais na avaliação PET e SPECT cerebrais na avaliação dos estados demenciais dos estados demenciais dos estados demenciais dos estados demenciais dos estados demenciais

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…Several research studies have evaluated samples of patients with AD relative to elderly controls using neurofunctional modalities such as FDG-PET and SPECT. The characteristic pattern found in AD is of hypometabolism/hypoperfusion in the temporoparietal cortex 10,11. A recent meta-analysis found that hypometabolism/hypoperfusion of the inferior parietal lobules and precuneus is the most consistent neurofunctional finding in AD in comparison with healthy elderly subjects 9.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several research studies have evaluated samples of patients with AD relative to elderly controls using neurofunctional modalities such as FDG-PET and SPECT. The characteristic pattern found in AD is of hypometabolism/hypoperfusion in the temporoparietal cortex 10,11. A recent meta-analysis found that hypometabolism/hypoperfusion of the inferior parietal lobules and precuneus is the most consistent neurofunctional finding in AD in comparison with healthy elderly subjects 9.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristic pattern found in AD is of hypometabolism/hypoperfusion in the temporoparietal cortex. 10 , 11 A recent meta-analysis found that hypometabolism/hypoperfusion of the inferior parietal lobules and precuneus is the most consistent neurofunctional finding in AD in comparison with healthy elderly subjects. 9 Moreover, longitudinal neurofunctional imaging studies have demonstrated hypometabolism/hypoperfusion in the parietal lobe of MCI converters in comparison with those who did not convert to AD.…”
Section: Introductionmentioning
confidence: 99%
“…A dose of a marker substance is injected intravenously (the radiopharmaceutical 18 FFDG) which takes about 45 minutes to be absorbed by the body. In the meantime, the patient should be kept in rest for 30 to 60 minutes and after this time, refer to the equipment where the test will be performed 14 .…”
Section: Pet-ct Interface and Epilepsymentioning
confidence: 99%
“…The detection of radiation transmitted by radiopharmaceuticals allows the early diagnosis of many diseases. In addition, it is a high sensitivity technique, where it is possible to obtain biological results and information with levels of biomarkers concentrations in nano or picomolar 14 .…”
Section: Pet-ct Interface and Epilepsymentioning
confidence: 99%
“…Algumas como a tomografia por emissão de pósitrons (PET) e a tomografia por emissão de fóton único (SPECT) são métodos de estudo das alterações do SNC há muitos anos, com extensa colaboração para o conhecimento e tratamento de algumas doenças neuropsiquiátricas como os transtornos afetivos e ansiosos, as demências, a esquizofrenia e a epilepsia (Kwock, 1998;Buchpiguel, 2000;Spinelli et al,2003). Em anos mais recentes, a RM vem ganhando cada vez mais espaço dentro da pesquisa no campo da neurociência.…”
Section: Epidemiologia Do Comprometimento Cognitivo Sem Demênciaunclassified